Effect of 5-Bromodeoxyuridine on Chromatin Transcription in Confluent Fibroblasts - Hill, Bridget T. (1974)
3T6 mouse fibroblasts were grown in 5-bromodeoxyuridine (BrdU) so that approximately 20% of the thymine residues in DNA were replaced by BrdU. BrdU replacement caused an alteration in the relative incorporation of labeled nucleotide precursors into RNA. The RNA synthesized by cells grown in BrdU has a lower proportion of adenine and a higher guanine complement. This was shown for (a) nascent RNA made in vivo by confluent monolayers of cells in culture; (b) RNA synthesized in vitro on a chromatin template with either homologous or heterologous RNA polymerase; and (c) RNA synthesized in vitro on a DNA template with a highly purified RNA polymerase. The product was completely digested by RNase. The relative decrease in the incorporation of adenine into RNA was reserved when BrdU-treated cells were allowed to proliferate in BrdU-free medium.